Textiles and clothing : an introduction to quality requirements in selected markets (ITC GenevaCH, 1994)
Examines current and envisaged European legislation on textiles and clothing and considers the impact of this legislation on manufacturers in general. Focuses on the quality requirement in the trading bloc represented by the European Economic area, although some consideration is also given to the North American market.
DC